Supporting self-esteem and self-acceptance in commercial brand campaigns created during a pandemic : Social and marketing aspects - Daszkiewicz, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Commercial brands are increasingly running campaigns supporting self-esteem and self-acceptance in response to social events, trends, and expectations related to social responsibility. By conducting such campaigns, brands try to pursue social and marketing objectives. The pandemic period was associated with increased problems and strengthening of social trends regarding self-acceptance and self-esteem. Therefore, the importance of actions related to these issues is of particular social relevance today. The pandemic conditions may have been reflected in the content and features of advertising campaigns and the associated consumer expectations and attitudes. In recent studies, far too little attention has been paid to intentional supporting self-esteem and self-acceptance in commercial brand campaigns. The article responds to an identified need for research concerning key messages and characteristic features of contemporary self-esteem advertisements, which may be linked to the specific social context. The important research issue is also the marketing and social value of advertising supporting self-esteem and self-acceptance. The article aims to identify key messages and features of commercial brand campaigns created during the pandemic that support self-esteem and self-acceptance. It also attempts to assess such campaigns in terms of their social and marketing value. These objectives were accomplished by using qualitative and quantitative methods. The research procedure involved three stages: desk research based on studies from the pandemic period regarding self-acceptance and self-esteem issues, a collective case study of campaigns of three brands supporting self-esteem and self-acceptance and a diagnostic survey using an online questionnaire on the consumer perception of such campaigns and their value judgments resulting from expectations, motives, and impact assessments. The research is placed in the context of a pandemic, but the trends identified, key messages and features of the self-esteem campaigns, and assessment dimensions may remain relevant in the future.
Keywords: self-esteem; self-acceptance; self-esteem advertising; self-esteem campaign; marketing campaign; commercial brand campaign; social campaign; socially responsible advertising; pandemic